Ma è davvero uno scandalo? Caravaggio sotto accusa ne L’olivo e l’olivastro di Vincenzo Consolo - Chmiel, Aneta (Romanica Silesiana)
Vincenzo Consolo, in one of his interviews, said that painting is counterbalance to style in his artistic work. In fact, the fine art is a frequent motif appearing in his works. The novel titled L’olivo e l’olivastro is a great example of this kind of narration since one of the chapters depicts Caravaggio’s stay in Siracusa, as well as the consequences of this fruitful visit. Taking into account the way an olive and a wild olive sprout from the same trunk, so as to be the symbol of everything that is cultivated and what is wild, it should be noted that in the same way the heroes in Caravaggio’s paintings have the features that characterize both human beings and animals. This split is present constantly in artistic work of Caravaggio who broke the cardinal rules set out in painting. As a result, he was called both a scandalmonger and the author of the first painting transgression, as well as a highly provocative artist. Vincenzo Consolo’s prose is thought-provoking and encourages reflection on relativity of goodness and beauty in the real world which is depicted as disappointing. Key words: Painting, escape, transgression, exaggeration, relativity.